2021
DOI: 10.1002/adem.202100468
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Induced Phase Transition and Defect‐Assisted Nonlinear Absorption and Optical Limiting in Nanorod Morphology V2O5 Thin Films

Abstract: Materials possessing nonlinear and saturable absorptions received significant interest due to their applicability in various novel technological applications such as optical limiting, Q-switching, upconversion lasing, and mode locking. [1][2][3][4] Nonlinear optical properties of materials like nonlinear and saturable absorptions are highly affected by localized defect states that alter the bandgap energy (E g ) in the structure. These states could be altered by changing the thickness of the material, doping t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 76 publications
(105 reference statements)
0
5
0
Order By: Relevance
“…According to the two‐temperature model, [ 33 ] e‐e thermalization is faster than e‐ph thermalization after light excitation. Phonons will indirectly obtain energy through e‐ph coupling, leading to a heated lattice [ 34 ] (Figure 3a). As a result, some materials show a transition in crystal morphology due to the increase in structural disorder, which will cause a reduction in E g and a difference in electrical conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…According to the two‐temperature model, [ 33 ] e‐e thermalization is faster than e‐ph thermalization after light excitation. Phonons will indirectly obtain energy through e‐ph coupling, leading to a heated lattice [ 34 ] (Figure 3a). As a result, some materials show a transition in crystal morphology due to the increase in structural disorder, which will cause a reduction in E g and a difference in electrical conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…This may be related to the localized defect states distribution inside the band gap. Our previous studies showed that defects have a great effect on the nonlinear absorption in amorphous and polycrystalline semiconductor thin films 59–61 . Polymer nanofibers, with enhanced scattering and prolonged path length (which increases light‐matter interactions), lead to enhanced nonlinear absorption.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies showed that defects have a great effect on the nonlinear absorption in amorphous and polycrystalline semiconductor thin films. [59][60][61] Polymer nanofibers, with enhanced scattering and prolonged path length (which increases light-matter interactions), lead to enhanced nonlinear absorption. It is clear that these properties will be different for different morphologies, which are strongly affected by the electrospinning process and material parameters such as solution concentration, polymer density, high voltage applied, solvent and molecular weight of the polymer.…”
Section: Nonlinear Optical Analysismentioning
confidence: 99%
“…The values of E U are calculated as 0.37, 0.17 and 0.15 eV for crystals 1, 2 and 3, respectively. Decreasing E U value with increase of the Mo/W ratio is the evidence of the decreasing defects in the structure [30,31].…”
Section: Linear Absorption Analysismentioning
confidence: 92%